2018
DOI: 10.1126/science.aao3136
|View full text |Cite
|
Sign up to set email alerts
|

Transcription-coupled changes in nuclear mobility of mammalian cis-regulatory elements

Abstract: To achieve guide RNA (gRNA) multiplexing and an efficient delivery of tens of distinct gRNAs into single cells, we developed a molecular assembly strategy termed chimeric array of gRNA oligonucleotides (CARGO). We coupled CARGO with dCas9 (catalytically dead Cas9) imaging to quantitatively measure the movement of enhancers and promoters that undergo differentiation-associated activity changes in live embryonic stem cells. Whereas all examined functional elements exhibited subdiffusive behavior, their relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
299
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(354 citation statements)
references
References 34 publications
36
299
1
Order By: Relevance
“…Another possibility would be the most processive RNA polymerase, which in the ~ 22 min that cohesin remains bound to DNA could extrude loops up to 875 kbp in length (assuming an average speed of 3.5 kbp/min; Wada et al , ). This possibility would also be in agreement with cohesin positioning being regulated by the very act of transcription (Busslinger et al , ) and its ensuing supercoiling (Racko et al , ), as well as by the increased mobility of genes and enhancers once they transition from an inactive to an active state (Gu et al , ). More recently, a model was proposed whereby simple diffusion, biased by multiple cohesin loading events at the same loading site, might be sufficient for loop extrusion and its prolongation (to explain Mbp‐long loops; Brackley et al , ).…”
Section: Ctcf and Cohesin In Insulation Loop Formation And Long‐ransupporting
confidence: 62%
See 2 more Smart Citations
“…Another possibility would be the most processive RNA polymerase, which in the ~ 22 min that cohesin remains bound to DNA could extrude loops up to 875 kbp in length (assuming an average speed of 3.5 kbp/min; Wada et al , ). This possibility would also be in agreement with cohesin positioning being regulated by the very act of transcription (Busslinger et al , ) and its ensuing supercoiling (Racko et al , ), as well as by the increased mobility of genes and enhancers once they transition from an inactive to an active state (Gu et al , ). More recently, a model was proposed whereby simple diffusion, biased by multiple cohesin loading events at the same loading site, might be sufficient for loop extrusion and its prolongation (to explain Mbp‐long loops; Brackley et al , ).…”
Section: Ctcf and Cohesin In Insulation Loop Formation And Long‐ransupporting
confidence: 62%
“…The prevalence of pre‐looped versus de novo enhancer–gene interactions during gene induction might be locus‐ and cell type‐dependent, with either permissive or instructive regulatory principles dominating, respectively. In this regard, the timely and robust first‐time encounters between genes and their cognate enhancers can be facilitated by either pre‐formed contacts (Ghavi‐Helm et al , ; Kolovos et al , ; Cruz‐Molina et al , ) or increased mobility due to the activity of the polymerase and/or cohesin (Busslinger et al , ; Gu et al , ). Finally, along a time course of B‐cell reprogramming, it is transcription factors like Nanog that instruct loop and TAD reorganization, often before changes in gene expression (Stadhouders et al , ), but always concomitant with chromatin remodeling and increased accessibility, which was shown to suffice for altering nuclear organization (Therizols et al , ).…”
Section: Transcription As a Looping Forcementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have provided evidence that the act of transcription may play a role in shaping chromatin organization [26,27,29,30,34,35], yet the global consequences of complete transcriptional arrest (i.e., blocking all three polymerases) on mammalian chromosomal architecture are not well understood. Accordingly, to assess whether genome organization is affected differently by the act of transcription compared to loss of steady-state RNA following RNase treatment, we treated K562 cells with actinomycin D (ActD), a drug that quickly (i.e., within 24 h) and irreversibly inhibits all polymerases and results in complete transcriptional arrest [36][37][38] ( Fig 1C).…”
Section: Experimental Strategy and Characterization Of Rnase Treatmenmentioning
confidence: 99%
“…Many long non-coding RNAs (lncRNAs) were thought to facilitate gene-regulatory functions, but systematic introduction of premature polyadenylation signals demonstrated that most lncRNAs are dispensable; instead, recruitment of transcription and splicing complexes drives their gene-regulatory function 15,16 . Recently, a "molecular stirring" model has been proposed wherein transcription increases molecular motion that drives enhancerpromoter interactions 17 . Similarly, we have proposed that RNA Polymerase II's (RNAPII) affinity for common co-factors or even itself could facilitate enhancer-promoter interactions 18,19 .…”
Section: Introductionmentioning
confidence: 99%